(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Copolymers of 9-anthrylmethyl and 9-anthrylethyl esters of methacrylic acid with N-vinylcarbazole and 3-iodo-N-vinylcarbazole were developed. For synthetized copolymers their spectral and electrophotographic properties were studied. Films based on these copolymers prossess more high photosensitivity in comparision with polyvinylcarbazole ones and can be applicated for hologramme recording.